Facebook como modificador del vocabulario y la cultura del habla en los estudiantes de primero a tercero de bachillerato de la Unidad Educativa Fiscomisional Mater Dei, provincia de Loja durante el periodo marzo-septiembre del 2021 - Muñoz Torres, Emily Salomé (2022)
The present research work seeks to analyze the incidence of social networks "Facebook as a modifier of vocabulary and culture of speech in students from first to third year of high school of the fiscomisional educational unit Mater Dei, province of Loja during the period March-September 2021”. The hypothesis raised in the present investigation is summarized in that, the publications they make on Facebook affect the cultural identity of young people, school of the fiscomisional educational unit mater Mater-Dei missionary fiscal school, since they adopt modified identities and linguistic expressions, similar to those that spread in the social network, affecting their social environment. To verify this hypothesis, a qualitative and quantitative methodology has been used, with techniques such as: surveys to contextualize the perception of students regarding the use of social networks and its impact on the modification of their cultural identity; observation sheets within the classroom, to check if the data of this coincide with the answers of the applied survey; and interviews with teachers, professionals and parents to delve into the study problem. From the results of this research, it will be possible to verify the use of social networks and mobile phones by students within community spaces (classroom, home, schoolyard, social gatherings). Keywords: social networks; identity, culture, personality, interpersonal communication; technology and internet